Teaching ESP online during the pandemic – a teachers’ perspective - Kic-Drgas, Joanna; Mureșan, Oana (Lingua Posnaniensis, 2022)
Due to the COVID-19 pandemic, teachers and educators have been forced to introduce digital solutions within a very short time, which influenced the educational perspective significantly, and required adapting to the new conditions, not only in what concerns teaching methods but also in terms of teaching content. Contrary to the commonly held opinion that teaching at tertiary level has not changed considerably, since it concerns adults who are already autonomous, the new teaching challenges have had an impact on tertiary education as well. Moreover, university teachers needed to face this new reality without prior preparation. The aim of this paper is to present the current pandemic-driven situation from the perspective of ESP teachers from various European countries by revealing not only some of the challenges posed by the pandemic, but also certain good practices which may become a guide for other ESP teachers. The methodology applied to inquiring this research question was a qualitative-quantitative online survey distributed among ESP teachers in European countries. The results show that online teaching during the pandemic was challenging for most respondents, at the same time offering them the opportunity to develop professionally by improving their technical skills and learning how to use online platforms, apps and tools.